Perancangan Media Pembelajaran Informatika Menggunakan Powtoon Di SMPN 2 Bukittinggi - Rizky Handayani Pasaribu; Hari Antoni Musril; Riri Okra; Sarwo Derta; Ryan Amanda (LPPM STIKI MALANG, 2023)
Informatics learning in class VII at SMPN 2 Bukittinggi experiences problems, namely students feel bored and waste time because they write too much material. so learning media such as learning videos are needed. This video was developed using powtoon. The research method used is Research and development (R&D) with the Planning, Production, Evaluation (PPE) development model. The results of this research produced a product in the form of a learning video created using Powtoon and accessed via the Linktree platform. The product test results show that the validity test involving 5 experts produced a score of 0.80 in the